Motivasi dan Interaksi Pada Pembelajaran Blended Learning - Seipah Kardipah; Basuki Wibawa (Jurnal Ilmiah Wahana Pendidikan, 2022)
Blended learning, which combines online and face-to-face learning, has become a common practice in higher education. The purpose of this research is to analyze the motivation and the interactions that occur in the blended learning. This study uses a qualitative and quantitative approach. Data were collected using questionnaires and interviews. The sample of this study were 24 students enrolled in the Computer Applications course. The results of this study indicate that students have confidence in learning (score 5.11). Students also have sufficient intrinsic motivation to undergo learning (score 5.26). In addition, students did not feel too anxious when following the lesson. Students also try to learn from mistakes when they fail the exam. Furthermore, even though they find it difficult to do the various assignments given, students prefer such (difficult) tasks to easy tasks. Interaction in the classroom occurs quite often because the lecturer walked around in the classroom to help students who were having difficulties. Online interaction also occured between lecturers and students which is one of the advantages of blended learning. Thus, blended learning can increase motivation and interaction if it is well designed and implemented consistently.